Information Technologies for Remote Monitoring of the Environment - Krapivin, Vladimir; Shutko, Anatolij M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The key novelty of this book is first of all in the successful attempt to conduct jointly modeling of environment in terms of physical environment related parameters and measuring similar parameters by means of multispectral remote sensing, primarily by means of passive microwave remote sensing technology. Another new step is in the development and utilization of a multilevel approach which includes remote sensing of the land and water parameters like soil moisture, depth to water table, biomass of vegetation, temperature and salinity of water, in situ measurements of similar parameters and incorporation of GIS and data sets into the models of typical environments. The part of book, which contains remote sensing is focused on multipurpose observations from aircraft obtained in many soil-climatic zones in different countries and is reach of the examples of practical application. Applied mathematicians, geophysics, hydrologists, socio-economists, statesmans and other researchers of environmental changes will find a wealth of information and ideas in this book.
1. Towards the information technology for environmental monitoring -- 2. Survivability and biocomplexity -- 3. The NSS model as the GIMS component -- 4. The GIMS-based study of ocean and sea ecosystems -- 5. Decision making procedure in the GIMS -- 6. Passive remote technologe and data processing algorithms -- 7. GIMS- based method for vegetation microwave monitoring -- 8. Remote sensing instruments and carrying platforms that realize the GIMS- technology.
Keywords: Environmental sciences; Remote sensing; Geographical information systems; Ecology; Environment; Environmental Monitoring/Analysis.; Remote Sensing/Photogrammetry.; Ecology; Geographical Information Systems/Cartography.; Energy, general